ANALISIS DAMPAK FENOMENA ‘MARRIAGE IS SCARY’ TERHADAP MINAT MENIKAH DI KECAMATAN SERANG BARU, BEKASI - Satriyanto, Hawa Mutiara; Oktaviani, Witia (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2025)
Abstract: The "Marriage is Scary" phenomenon among younger generations reflects a shift in how marriage is perceived, not as a key life achievement, but as a source of anxiety and uncertainty. This trend is reinforced by high digital media consumption, as seen in Serang Baru District, Bekasi, an area with significant internet and social media use. This study aims to analyze the factors behind the emergence of the "Marriage is Scary" phenomenon, its impact on interest in marriage, and the Indonesian government's response. A qualitative method with a case study approach was used. Data were collected through observation, interviews, and documentation, then analyzed using Creswell’s thematic analysis model, which includes coding, theme identification, interpretation, and integration with relevant literature. To ensure validity, data triangulation from multiple sources was applied. The findings reveal that fear of marriage among youth in Serang Baru is influenced by five main factors: economic instability, social pressure, social media influence, emotional instability, and traumatic personal experiences. These factors contribute to a declining interest in marriage, marked by delayed decisions and greater selectivity in choosing a partner. The study also found that while the Indonesian government has responded through premarital education and legal protections for women, it has not explicitly addressed the "Marriage is Scary" narrative. Keywords: Marriage is Scary; Interest in Marriage, Marriage Phenomenon.